A counterexample to a Penrose inequality conjectured by Gibbons - Dain, Sergio Alejandro (2011)
We show that the Brill–Lindquist initial data provide a counterexample to a Riemannian Penrose inequality with charge conjectured by Gibbons. The observation illustrates a sub-additive characteristic of the area radii for the individual connected components of an outermost horizon as a lower bound of the ADM mass.